A Work study on Playpen Export Philippines - Ibarra, Ma. Celeste A.; Leung, Ma. Felicia P.; Magpili, Luna Mylene M. (Diliman, Quezon City College of Engineering, 1992)
Playpen Export Philippines was established in August 1, 1991 to engage in the production and exportation of children's clothes. The company exports its products to Germany and Canada which presently represent its major markets. Management is headed by Ms. Christine del Rosario who is the General Manager of Playpen. Amidst stiff competition posed by its foreign counterparts, the firm's exporting business is continually faced with rigid quality standards and tight timetables in order for the company to meet its sizeable orders on time. The company is characterized by a low productivity level traceable to the following factors : 1. lack of machines as the company is restrained from upgrading/replacing its existing/old facilities due to the limited allocation of funds; 2. low productivity of workers due to insufficient incentives, poor salary structure, and bad working conditions. As there continue to dampen their morale, the absence of any performance evaluation likewise makes the workers complacent with the performance of their jobs and responsibilities, hence the drop in productivity; 3. inefficient methods due to poor scheduling/time management, lack of line balancing, improper layouting and utilization of inappropriate materials and equipment in production; 4. production mismanagement particularly with regards to poor layout procedures and absence of definite policies and guidelines; Consequently, Playpen's low productivity hamper overall work flow in the plant, thereby resulting in delays in production shipments. This therefore damages the firm's goodwill, hence, resulting in decreased orders from its major customers. Moreover, the delays lead to higher rejection rates which incur huge unnecessary costs for the company. As a result of the enormous costs, net return/profitability thereby decreases. In order to increase productivity and profitability of the firm, changes in methods, and systems and procedures are therefore recommended. These are : 1. setting permanent policies and procedures which include work standardization, higher incentives for workers, strict attendance of all employees and others; 2. rearrangement of departments/work area to minimize movement and to facilitate smooth and faster flow of work in both the administration and production area; 3. practicing regular evaluation of workers and their performances; Furthermore, additional equipments such as edging machines are needed to prevent the flow of work to clog. Also, ceiling and additional light are needed to improve working condition and therefore increase the efficiency of workers.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Playpen Export Philippines; Clothing trade and industry; Foreign trade; Systems analysis